Precession of the Earth's Axis - Mallik, Arbind Kumar (Himalayan Physics, 2011)
Not available. Key words: Earth's Axis The Himalayan Physics Vol.1, No.1, May, 2010 Page: 83-84 Uploaded Date: 29 July, 2011